Resistencia a herbicidas en malezas asociadas con arroz - Fischer, Albert; Valverde, Bernal E. (International Center for Tropical Agriculture, 2010)
Resistance to herbicides in weeds associated with rice The factors determining the evolution of resistance to herbicides in weeds are analyzed as well as the criteria used to detect this evolution and the mechanisms of resistance to herbicides in weeds. Several concepts on the prevention of the appearance of weeds and their management are discussed, with special emphasis on the rice crop. Factors causing yield losses in rice as well as increased production costs and environmental risks include the following: the evolution of the resistance to several herbicides in weed populations, which has been favored by the monocropping of rice; the strong dependence of farmers on chemical weed control; and the repeated application of the same type of herbicide. Factors determining the rate of evolution of weed resistance to herbicides are the initial frequency of resistant (mutant) individuals, their fecundity and longevity in the soil reservoir, their ecological fitness, the reproduction mode, the genetic base and mode of inheritance of the resistant trait, the toxicity and residuality of the herbicide, and herbicide dosage and frequency of use. This selection pressure, which favors the appearance of resistant weed biotypes, can be reduced by using a sequence of herbicides or by combining herbicides with different modes of action and degradation mechanisms. Other practices, such as planting weed-free certified seed, field inspection, and trials to detect resistant biotypes, help limit the dispersal of herbicide-resistant biotypes. Metabolic resistance as well as the evolution of multiple resistance represent challenges that will require creative management strategies and underscore the need for integrated weed management. Models to predict the evolution of resistance are useful research tools and allow for the design and selection of profitable integrated weed management programs. The management of the resistance to herbicides requires long-term planning and the support of educational programs.